PERAN CARE DALAM MENINGKATKAN KESETARAAN GENDER DALAM BIDANG PENDIDIKAN MELALUI PROGRAM PERSONAL ADVANCEMENT AND CAREER ENHANCEMENT (PACE): Studi Kasus Provinsi Jawa Barat Periode 2019 - 2022 - Shabira Arsa Ghalda, (2023)
This research discusses the role of the international organization (NGO) CARE Indonesia in increasing gender equality in the education sector through the Personal Advancement and Career Enhancement (PACE) program in Indonesia in the case study of West Java Province. Indonesia is one of the countries with a low level of gender equality. One of the causes of low gender equality in Indonesia is the thick patriarchal culture in Indonesia. In several journals, it is said that the root of gender inequality lies in the education sector. Inequality in the education sector has become the main factor that has the most influence on gender inequality as a whole. Gender equality in education can be realized through synergy between institutions, both at state government agencies or national foundations/organizations to the community, one of which is the NGO CARE Indonesia which focuses on gender equality and social inclusion. The program run by CARE is the Personal Advancement and Career Enhancement (PACE) program. This research uses descriptive qualitative methods and research techniques through observation, interviews, and literature study in answering research problems.